2015
DOI: 10.1128/jcm.00470-15
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Epidemiology of Methicillin-Resistant Staphylococcus aureus in a Neonatal Intensive Care Unit in the Decade following Implementation of an Active Detection and Isolation Program

Abstract: 1, 2). The National Nosocomial Infections Surveillance System observed a Ͼ300% increase in the incidence of late-onset MRSA infections in NICUs, from 0.7 to 3.1 infections/10,000 patient days, between 1995 and 2004 (3). Unique host and environmental factors, including immature immune systems, high frequency of contact with health care providers (4), exposure to numerous invasive procedures, NICU overcrowding and understaffing (5, 6), and prolonged hospitalization (7), make NICU patients at especially high risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 33 publications
5
35
3
Order By: Relevance
“…Notwithstanding an active surveillance and isolation program and standardized decolonization protocol, nearly 4% of the infants in our NICU were colonized with MRSA over the study period, consistent with previous NICU studies in the U.S. [9, 25]. Within our study cohort, the predominant colonizing strains were CA-MRSA, and infants colonized with these CA-MRSA strains developed infections more quickly than infants colonized with traditional HA-MRSA strains.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Notwithstanding an active surveillance and isolation program and standardized decolonization protocol, nearly 4% of the infants in our NICU were colonized with MRSA over the study period, consistent with previous NICU studies in the U.S. [9, 25]. Within our study cohort, the predominant colonizing strains were CA-MRSA, and infants colonized with these CA-MRSA strains developed infections more quickly than infants colonized with traditional HA-MRSA strains.…”
Section: Discussionsupporting
confidence: 86%
“…This risk, as well as the potential for colonized neonates to serve as reservoirs for transmission to other vulnerable patients within the NICU, has prompted a focus on infection prevention measures to decrease MRSA colonization rates [9, 13, 14]. While cohorting, isolation, and contact precautions are effective in reducing MRSA prevalence rates [25], many U.S. centers, upon identifying an MRSA colonized patient, employ topical antimicrobials in an effort to eradicate MRSA carriage and thereby prevent MRSA transmission and infection [27, 28]. Among adult patients, the practice of universal chlorhexidine bathing has yielded success in reducing the incidence of MRSA infection in ICUs compared to surveillance and isolation alone [29].…”
Section: Discussionmentioning
confidence: 99%
“…14 Both methicillin-sensitive S. aureus (MSSA) and MRSA are associated with chorioamnionitis and neonatal sepsis, lactational mastitis, breast abscess, perineal abscess, and infections associated with laceration/episiotomy as well as surgical site infection after cesarean birth. [14][15][16][17][18][19][20][21][22][23][24][25] The bacterium is also commonly seen during pregnancy as an SSTI.…”
mentioning
confidence: 98%
“…Procedures and devices such as endotracheal intubation and mechanical ventilation 6,16,24,26) , percutaneous central venous catheterization 16) , and parenteral feedings 16) are also known to be risk factors for MRSA infection. In a recent study, outborn infants were also described as a risk factor for MRSA colonization 5) .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, the prevalence of MRSA colonization upon admission was 1.5% (95% confidence interval [CI] 0.9-2.2) among NICU patients 5) . Several factors contribute to NICU patients being at a particularly high risk of being colo nized and infected with MRSA, including an immature immu ne system, exposure to numerous invasive procedures 6) , prolonged hospitalization 7) , and, especially, a high frequency of contact with health care providers 8,9) . It has been reported that MRSA colonization or infection is associated with mortality in the NICU 10) .…”
Section: Introductionmentioning
confidence: 99%